'Surrogate decision-making' in India for women competent to consent and choose during childbirth. Issue 3 (3rd July 2021) - Mayra, Kaveri; Matthews, Zoë; Sandall, Jane
Abstract: In a postcolonial, deeply patriarchal culture, decisions are often made for Indian women about every aspect of their life – beginning with whether they will be allowed to be born. This is followed by every life decision, including education and marriage. A 'surrogate decision-maker' is a guardian who decides for an adult incapable of making their own decisions due to a mental health condition, or as a substitute based on a patient's stated or predicted wishes. However, the majority of Indian women are 'controlled' and 'allowed' or otherwise regarding everything. No choice in women's life is women's own, including decisions about deeply personal experiences such as giving birth. Our article is embedded in feminist epistemology and uses voice-centred relational analysis of interviews with four women from impoverished backgrounds in Bihar, India, to explore decision making around childbirth and throughout their lives. The surrogate decision-makers in the birth environment are: 1) healthcare and non-healthcare providers, and/or 2) family members (who play the dominant role in every other decision about women's lives). They communicate amongst themselves about a woman's active bodily experience. Through I-poems we present women's varied levels of resistance and non-resistance to obstetric violence, which can be looked at as an extension of their response to violence in their routine lives. We find similarities in women's conditioning to endure, and argue that women should be the key stakeholders of their decisions about themselves and their bodies, which includes decisions about birth.